Genetic Polymorphisms of 22 Novel Autosomal Short Tandem Repeat Loci in Sierra Leone Population - Yi Liu; Chudong Wang; Dan Wen; Weifeng Qu; Hao Xing; Hongtao Jia; Ruyi Xu; Xuan Tang; Siqi Chen; Jienan Li; Guanlin Li; Lagabaiyila Zha; et al. (Wolters Kluwer Medknow Publications, 2024)
Background: Exploring and identifying novel alleles of noncombined DNA Index System (CODIS) short tandem repeat (STR) loci in different ethnic groups is important for the establishment of forensic reference databases and study of population genetics. AIM: This study is aimed to explore the genetic polymorphism of 22 non-CODIS autosomal STR loci (D6S477, D18S535, D19S253, D15S659, D11S2368, D20S470, D1S1656, D22-GATA198B05, D8S1132, D4S2366, D21S1270, D13S325, D9S925, D3S3045, D14S608, D10S1435, D12S391, D7S3048, D17S1290, D5S2500, D2S1338, and D16S539) in Sierra Leone population and analyze the population genetic relationships in comparison with other populations. MATERIALS AND METHODS: The samples of a total of 495 unrelated individuals (274 females and 221 males) from Sierra Leone were examined by the Microreader™ 23SP ID System, and their genetic polymorphisms and associated forensic parameters were calculated. The genetic relationships between Sierra Leone population and other populations were evaluated as well. Results: A total of 287 alleles were observed with allelic frequencies ranging from 0.001 to 0.399. The cumulative power of discrimination (CPD) of the 22 autosomal STR loci was 0.999999999999999 99999999999999538. The cumulative probability of exclusion (CPE) of the 22 autosomal STR loci was 0.9999998514 (CPEdous) and 0.999999 9999826 (CPEtrios). All of the STR loci reached the Hardy-Weinberg equilibrium after Bonferroni correction. The population genetics analysis results demonstrated that Sierra Leone population exhibited distinctive genetic characteristics compared to those of East Asian populations and it had relatively close genetic distances to the Uygur population. Conclusion: The results of this study could enrich the forensic databases with Sierra Leone population. The 22 STR loci are highly polymorphic and could be used for forensic practice and population genetics studies.